2013
DOI: 10.1186/1471-2164-14-663
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate utilization and metabolism is highly differentiated in Agaricus bisporus

Abstract: BackgroundAgaricus bisporus is commercially grown on compost, in which the available carbon sources consist mainly of plant-derived polysaccharides that are built out of various different constituent monosaccharides. The major constituent monosaccharides of these polysaccharides are glucose, xylose, and arabinose, while smaller amounts of galactose, glucuronic acid, rhamnose and mannose are also present.ResultsIn this study, genes encoding putative enzymes from carbon metabolism were identified and their expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 66 publications
(78 reference statements)
4
51
1
2
Order By: Relevance
“…As expected, a decrease in total carbohydrate content (30% w/w based on dry matter (DM)), both xylan (40% w/w) and glucan (23% w/w), was observed in compost from Filling to 2 nd flush, indicating that carbohydrates were metabolized during the fruiting of A. bisporus. These results were in agreement with gene expression levels of A. bisporus during fruiting body formation showing that both the hexose and pentose catabolic pathway were upregulated (Patyshakuliyeva et al, 2013). Previously, it was reported that if compost of PII was compared with 1 st flush of mushrooms, which also includes carbohydrate consumption during mycelium growth (16 days (PIII)), a decrease of 50% (w/w DM) of carbohydrates was reported (Iiyama et al, 1994).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…As expected, a decrease in total carbohydrate content (30% w/w based on dry matter (DM)), both xylan (40% w/w) and glucan (23% w/w), was observed in compost from Filling to 2 nd flush, indicating that carbohydrates were metabolized during the fruiting of A. bisporus. These results were in agreement with gene expression levels of A. bisporus during fruiting body formation showing that both the hexose and pentose catabolic pathway were upregulated (Patyshakuliyeva et al, 2013). Previously, it was reported that if compost of PII was compared with 1 st flush of mushrooms, which also includes carbohydrate consumption during mycelium growth (16 days (PIII)), a decrease of 50% (w/w DM) of carbohydrates was reported (Iiyama et al, 1994).…”
Section: Discussionsupporting
confidence: 88%
“…Apparently, A. bisporus did not degrade these remaining substituted xylan fragments. That conclusion was supported by the result that the two genes annotated as putative ␣-glucuronidases (both GH115, Patyshakuliyeva et al, 2013Patyshakuliyeva et al, , 2015 were not expressed in the same compost samples as used to analyze the resistant substituted xylans. In addition, A. bisporus genes from family GH43 were assessed for similarity to two genes known to encode biochemically characterized AXH-d3 activity featuring the release of arabinose from xylosyl residues doubly substituted with arabinosyl residues.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations